Inhibitory Effects of Donkey Hide Gelatin on DNCB-Induced Atopic Dermatitis in NC/Nga Mice - Lee, Ju Hyun; Dong, Linsha; Noh, Hyeon Min; Park, Sung-Gu; Kim, Seung-Hyung; Jo, Eun Heui; Lee, Dong-Sung; Park, Min Cheol (Frontiers in Pharmacology, 2022)
The increase of atopic dermatitis has led to higher socio-economic cost and raised a need for alternative medicine as novel therapeutic agents. In this study, we aimed to evaluate the inhibitory effects of Donkey Hide Gelatin (DHG) water extract on DNCB-induced atopic dermatitis in NC/Nga mice and on tumor necrosis factor (TNF)-α/interferon (IFN)-γ-treated keratinocytes and to investigate its underlying molecular mechanisms. NC/Nga mice were induced by DNCB, administered Dexamethasone (3 mg/kg) or DHG water extracts (100 - 400 mg/kg) for 3 weeks. The skin symptom score, serum IgE and immune cells were measured, the ALN, spleen and dorsal skin tissue were extracted for FACS, quantitative real-time PCR and histology analysis. In vitro, HaCaT cells were induced by TNF-α/IFN-γ, the levels of pro-inflammatory cytokines and chemokines and its underlying mechanism were measured by ELISA and Western blot. As a result, DHG groups showed a significant decrease in the skin symptom score and the immune cell absolute number. It also showed a marked reduction of allergic and the levels of neutrophils and eosinophils in histology analysis. In TNF-α/IFN-γ induced HaCaT cells, DHG showed inhibition effects on IL-6, IL-8, TARC and RANTES, it also downregulated the expression of ICAM-1 and COX-2, up-regulated the expression of Filaggrin. Furthermore, DHG suppressed the activation of NF-κB and mitogen-activated protein kinases (MAPK) signaling pathway induced by TNF-α/IFN-γ. Taken together, DHG maybe a potential therapeutic agent or supplement for skin inflammatory disease such as atopic dermatitis.